THE RELATIONSHIP BETWEEN THE LONG TIME ON HEMODIALISIS AND THE LEVEL OF DEPRESSION IN CHRONIC KIDNEY FAILURE PATIENTS IN THE HEMODIALISIS ROOM SANTOSA HOSPITAL BANDUNG CENTRAL (SHBC) - Handayani, April; Somana, Aan; Isaiah , Octavina; Susanto, Ijun Rijwan (jfpublisher, 2024)
Introduction. The prevalence of depression cases in the world is around 17% of all mental disorders in society. This figure is the largest compared to other mental disorders. This condition will increase under certain conditions, for example in patients with certain medical conditions who experience chronic illnesses such as stroke, diabetes, cancer and chronic kidney failure. Patients with chronic kidney failure who are required to undergo hemodialysis will increase the risk of depression, this is caused by stressors that arise such as dependence on hemodialysis machines for life, changes in lifestyle patterns related to long periods of undergoing hemodialysis, restrictions on food and drink patterns and adaptation to disease condition. The aim of this study was to determine the relationship between the length of time undergoing hemodialysis and the level of depression in chronic kidney failure patients in the SHBC hemodialysis room. Method. This research is a quantitative correlation research with a cross sectional approach or also called a point time approach . The sampling technique used in this research was Accidental Sampling of 92 respondents using the Beck Depression Inventory (BDI) questionnaire. Result & Analysis. Based on the results of statistical tests, the p-value = 0.038 (p <0.05). Discussion. In this study, it can be concluded that there is a relationship between the length of time undergoing hemodialysis and the level of depression in chronic kidney failure patients in the SHBC hemodialysis room in 2022. Patients with chronic kidney failure have many stressors that arise while undergoing hemodialysis, for this reason families and nurses can provide motivation to patients with chronic kidney failure so that they can reduce the level of depression.